ETHNOMATHEMATICS EXPLORATION OF THE MALAKA CULTURE OF THE TETUN TRIBE COMMUNITY IN MALAKA REGENCY - Roswita Lioba Nahak; Viktorius Paskalis Feka (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
The culture of giving children called ‘matamusan’ from the Tetun tribe is a local culture that should be for its authenticity and sacredness. The procession of determining the children of ‘matamusan’ contains ethnomathematical values not realized by the cultural legatees. This research aims to explore the ethnomathematical elements in ‘matamusan’ culture. In addition, this research can be beneficial at developing context-based mathematical learning materials and a reference in developing the operational curriculum of the education units in the autonomous learning curriculum, particularly in elementary schools. This research employs a qualitative-exploratory method using an ethnographic approach, while observation and interviews are used as techniques to collect data. Data analysis uses data reduction, data presentation, and conclusion. The results of this research show that there are six mathematical concepts  in the cultural procession of determining ‘matamusan’ children: (1) the concepts of one-dimensional geometry, namely a line consisting of horizontal lines, parallel lines, and acute angles, and two-dimensional geometry, namely rectangles and rhombus. (2) the concept of counting; 3) the concept of the median; 4) the concept of the unit of time; 5) the concept of the unit of weight and; 6) the concept of currency, which can be used to develop teaching materials on mathematical content, especially in elementary schools whose implementation is in the form of context-based mathematical problems..